The posterior reversible encephalopathy syndrome: what's certain, what's new?. Issue 3 (5th May 2011) - Roth, C; Ferbert, A
Abstract : The posterior reversible encephalopathy syndrome is an increasingly recognised disorder. Most patients have several symptoms; seizures are the most frequent, often multiple or status epilepticus. A combination of seizures, visual disturbance and/or headache, in particular, should lead to an early brain MRI to reveal the typical pattern of bilateral hyperintensities on fluid attenuated inversion recovery imaging, predominantly in the parieto-occipital region. There seem to be many possible triggers, including abrupt arterial hypertension, impaired renal function, pregnancy, immunosuppressive therapies and various inflammatory conditions. The clinical outcome is excellent, with recovery within a few days, while the MRI abnormalities resolve much more slowly. Little is known about the best management. Seizures do not normally progress to chronic epilepsy so antiepileptic drugs should be discontinued after about 3 months.